The Implications of The Flipped Learning Model on Students' Critical Thinking Skills and Creativity - Sayadi, Nuril Huda, Sri Utami (Journal of Educational Studies, 2025)
It is crucial for classroom instruction to foster pupils' capacity for original thought and analysis. Various points of view may be evaluated by students who possess strong critical thinking abilities. At the same time, encouraging kids to think outside the box encourages them to come up with novel ideas and approaches to old challenges. In this study, we'll look at how TBSM SMKN 2 Pamekasan's tenth graders used the flipped classroom concept to foster more critical thinking and creative thinking among their peers. Students' poor levels of critical thinking and creativity in response to course content are shown by this study's observations of grade XI students at SMKN 2 Pamekasan. In this quantitative investigation, the Non-Equivalent Pre-test Post-test Control Group approach was used as a quasi-experimental approach. The overarching goal of this design was to determine if and to what degree the flipped classroom approach significantly improved students' capacity for creative and critical thinking. Information was gathered from several sources, including lesson plans, assessments, and observation sheets. It was then subjected to a battery of tests in IBM SPSS version 2.0.1 for Windows, including validity, reliability, difficulty level, discrimination power, and hypothesis testing using the MANOVA approach. The findings demonstrated that students' critical thinking abilities may be enhanced by 42.4% inside the flipped learning paradigm, as shown by the R-squared value of 0.423, or 42.3%. Student creativity had an R-squared value of 0.282, or 28.2%, suggesting that students' critical thinking abilities may be enhanced by 28.2% using the flipped learning methodology. This revolutionary learning technique may be utilised to increase the quality of both the learning process and learning results. The flipped learning model has been proved to have a favourable influence on students' critical thinking and creative abilities.